Analisis Yuridis Penyelenggaraan Izin Pemanfaatan Ruang (Study Pada Penyusunan Peraturan Daerah Tentang Izin Pemanfaatan Ruang Kabupaten Labuhan batu) - Yuli Rosdiana (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Control of spatial use is as an integral part of the spatial planning process. The use of space in various regions in Indonesia, in its implementation is often or not in line with the stipulated spatial plan. Several factors that influence the discrepancy include pressure on market development towards space, unclear control mechanisms and weak law enforcement against violations that occur. The tendency of spatial use deviations can occur because the spatial plan product does not pay attention to the implementation aspects or vice versa that spatial use is less concerned with the spatial plan that has been set. This writing uses normative juridical legal research methods (normative research), namely legal research conducted by examining library material or secondary data. The research specifications in this writing are descriptive analytical research. Descriptive is to show the comparison or relationship of a set of data with another set of data, and the purpose is to provide an overview, examine, explain and analyze. The Impact of Regional Regulations on Permit for Spatial Utilization of regional finance will cover two things, namely increasing regional income sources and burdening finance area.